The genus Lyroda Say, 1837 in Africa and Arabian Peninsula with description of two new species (Hymenoptera, Crabronidae) - Schmid-Egger, Christian; Jahdhami, Ali Al- (Zootaxa, 2021)
The genus Lyroda Say, 1837 is reviewed in Africa and Arabia. Lyroda centralafricana Schmid-Egger & Al-Jahdhami, sp. nov. is described from Central African Republic and Zambia from both sexes; the holotype is a male. Lyroda salalah Schmid-Egger & Al-Jahdhami, sp. nov. is described from Oman in both sexes; the holotype is a female. The unknown male of L. aethiopica is described for the first time. A key to Lyroda species from Africa and the Arabian Peninsula is given.